2013
DOI: 10.3389/fninf.2013.00024
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of transfer entropy and inter-hemispheric brain functional connectivity in patients with disorder of consciousness

Abstract: Severe traumatic brain injury can lead to disorders of consciousness (DOC) characterized by deficit in conscious awareness and cognitive impairment including coma, vegetative state, minimally consciousness, and lock-in syndrome. Of crucial importance is to find objective markers that can account for the large-scale disturbances of brain function to help the diagnosis and prognosis of DOC patients and eventually the prediction of the coma outcome. Following recent studies suggesting that the functional organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…23 Interhemispheric connectivity was reduced when seeds were set in the precentral gyrus, postcentral gyrus and intraparietal sulcus, or across the brain. 22,28 In a study in which seeds were placed in the thalamus, patients in VS demonstrated a greater reduction in connectivity of the nonspecific thalamic connections of the intralaminar nuclei associated with the ascending reticular activating system than in the specific thalamic connections related to the thalamic sensory and motor relay functions. 34 Brain network topology was assessed through graph theoretical approaches in several studies.…”
Section: Systematic Review Population Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Interhemispheric connectivity was reduced when seeds were set in the precentral gyrus, postcentral gyrus and intraparietal sulcus, or across the brain. 22,28 In a study in which seeds were placed in the thalamus, patients in VS demonstrated a greater reduction in connectivity of the nonspecific thalamic connections of the intralaminar nuclei associated with the ascending reticular activating system than in the specific thalamic connections related to the thalamic sensory and motor relay functions. 34 Brain network topology was assessed through graph theoretical approaches in several studies.…”
Section: Systematic Review Population Characteristicsmentioning
confidence: 99%
“…40 Other neuronal systems in which decreased functional connectivity was noted in patients with DOC included left and right executive control, auditory, and attention networks. 18,21 Six studies evaluated functional connectivity using seedbased correlative analysis [22][23][24]28,34,40 (table e-3). Intrinsic connectivity of the DMN was found to be decreased in patients with MCS and VS, 23,40 while extrinsic connectivity between DMN and limbic structures was increased.…”
Section: Systematic Review Population Characteristicsmentioning
confidence: 99%
“…We applied resting fMRI preprocessing similar to previous work (Alonso-Montes et al, 2015;Amor et al, 2015;Diez, Erramuzpe, et al, 2015;Diez, Bonifazi, et al, 2015;Diez et al, 2017;Mäki-Marttunen, Diez, Cortes, Chialvo, & Villarreal, 2013;Marinazzo et al, 2014;Rasero, Pellicoro, et al, 2017;Stramaglia et al, 2016Stramaglia et al, , 2017Stramaglia, Angelini, Cortes, & Marinazzo, 2015) using FSL and AFNI (http://afni.nimh.nih.gov/afni/). First, slice-time correction was applied to the fMRI data set.…”
Section: Functional Mrimentioning
confidence: 99%
“…Unusual material properties-such as superconductivity, metal-insulator transitions, and heavy fermions-have been attributed to collective behavior arising from the compounded interaction of system components [1]. Collective behavior is by no means limited to complex materials, however: the behavior of financial markets [2], epileptic seizures [3] and consciousness [4], and animal flocking behavior [5] are all also seen as examples. We now appreciate that it appears most prominently via phase transitions ( [6] and references therein).…”
Section: Introductionmentioning
confidence: 99%